2019
DOI: 10.1111/tops.12457
|View full text |Cite
|
Sign up to set email alerts
|

The Inferential Language Comprehension (iLC) Framework: Supporting Children's Comprehension of Visual Narratives

Abstract: We present an integrated theoretical framework guiding the use of visual narratives in educational settings. We focus specifically on the use of static and dynamic visual narratives to teach and assess inference skills in young children and discuss evidence to support the efficacy of this approach. In doing so, first we review the basis of the integrated framework, which builds on major findings of cognitive, developmental, and language research highlighting that (a) inference skills can be developed in non‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 61 publications
4
29
0
4
Order By: Relevance
“…Finally, in discussing myths, we made the case that being a fluent reader of drawn sequential narratives requires exposure. In many cultures, children’s first exposure to reading is through multimodal visual narratives, and various works have suggested that visual narratives might be beneficial for literacy, language learning, and inferences (Kendeou et al, ). Yet, as discussed above, understanding of visual narratives themselves does not come “for free” with visual perception and event cognition, and requires a fluency developed with exposure and practice.…”
Section: Aspects Of Visual Narrativesmentioning
confidence: 99%
“…Finally, in discussing myths, we made the case that being a fluent reader of drawn sequential narratives requires exposure. In many cultures, children’s first exposure to reading is through multimodal visual narratives, and various works have suggested that visual narratives might be beneficial for literacy, language learning, and inferences (Kendeou et al, ). Yet, as discussed above, understanding of visual narratives themselves does not come “for free” with visual perception and event cognition, and requires a fluency developed with exposure and practice.…”
Section: Aspects Of Visual Narrativesmentioning
confidence: 99%
“…Whether written, drawn, or filmed, narratives require complex cognitive skills like processing narrative structure (Cohn, ; Cohn et al, ), segmenting a story into events (Cohn & Bender, ; Magliano, Kopp, McNerney, Radvansky, & Zacks, ), and constructing a mental model of the unfolding story (Magliano & Zacks, ; Zwaan & Radvansky, ). Like linguistic narratives, visual narratives require inference generation and the ability to “fill in the gap” between narrative events (Cohn, ; Cohn & Kutas, ; Cohn & Wittenberg, ; Magliano, Larson, Higgs, & Loschky, ; McCloud, ; see also Kendeou et al, ), which may be difficult for individuals with certain cognitive disorders.…”
Section: Additional Limitations Of the Visual Ease Assumptionmentioning
confidence: 99%
“…For instance, developmental trajectories of sequential image understanding are concurrent with those of ToM development (Bornens, ; Cohn, ; Wellman, Cross, & Watson, ), creating issues if visual narratives are used to assess ToM in children. Yet few studies using visual narratives as stimuli have assessed participants’ proficiency with this medium (see also Kendeou et al, ). One potential tool for such an assessment is the Visual Language Fluency Index (VLFI), which estimates participants’ proficiency with reading and drawing comics.…”
Section: Additional Limitations Of the Visual Ease Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inference has been a primary focus of studies of discourse (McNamara and Magliano 2009), especially in research on how we understand visual narratives, like comics or picture stories (Cohn 2020;Loschky et al 2020;McCloud 1993;Saraceni 2016). Research on verbal narrative has often used visual narratives as stimuli, assuming them to involve or evoke similar inferential processing (Gernsbacher et al 1990;Loschky et al 2020;Magliano et al 2019), and visual narratives have even been posited as tools for bootstrapping verbal inferential abilities (Kendeou et al 2020). Yet, little research exists on the neurocognition of visual narrative inferencing itself.…”
Section: Introductionmentioning
confidence: 99%